Is obesity treated like a contagious disease?. Issue 4 (27th December 2019) - Tapp, Caley; Oaten, Megan; Stevenson, Richard J.; Occhipinti, Stefano; Thandi, Ravjinder
Abstract: The behavioral avoidance of people with obesity is well documented, but its psychological basis is poorly understood. Based upon a disease avoidance account of stigmatization, we tested whether a person with obesity triggers equivalent self‐reported emotional and avoidant‐based responses as a contagious disease (i.e., influenza). Two hundred and sixty‐four participants rated images depicting real disease signs (i.e., person with influenza), false alarms (i.e., person with obesity), person with facial bruising (i.e., negative control), and a healthy control for induced emotion and willingness for contact along increasing levels of physical proximity. Consistent with our prediction, as the prospect for contact became more intimate, self‐reported avoidance was equivalent in the influenza and obese target conditions, with both significantly exceeding reactions to the negative and healthy controls. In addition, participants reported greatest levels of disgust toward the obese and influenza target conditions. These results are consistent with an evolved predisposition to avoid individuals with disease signs. Implicit avoidance occurs even when participants know explicitly that such signs—here, obese body form—result from a noncontagious condition. Our findings provide important evidence for a disease avoidance explanation of the stigmatization of people with obesity.